Stilistika dan Tafsir: Memahami Variasi Stile dalam Tafsir Rahmat Oemar Bakry - Amatullah, Nur Afra Afifah Amani (Sunan Kalijaga Islamic State University, 2023)
The works of tafsir in Indonesia, from before to after independence, reflect the socioeconomic and cultural situations of the writers and readers, as seen by the employment of numerous scripts such as Arabic, Cacarakan, Jawi, Latin, Lontara, and Pegon. This study analyzes style changes in Oemar Bakry’s Tafsir Rahmat, specifically interpreting Q.S. An-Nisā’ [4]: 15-18. This study used a stylistic technique to detect four types of stile variation in Tafsir Rahmat: word choice, sentence type variation, rhetorical writing style, and cross-referencing. The study discovered that, in addition to script, style variety influences the character of tafsir compositions. Although prior research has focused on language, script, and specific themes in tafsir works, the study of stylistic differences in Tafsir Rahmat remains limited. The analysis results reveal that stile changes not only simplify message delivery, but also enhance the beauty of language in interpretation. This study contributes significantly to the study of tafsir by emphasizing the role of stylistic variation in the efficiency of tafsir communication.